Töötervishoid : kaheksa valdkonda Euroopa Ühenduse poliitika jaoks - Vogel, Laurent (Brussels, 2004)
"EU enlargement raised many questions about the future of health at work policy. There has been progress in cutting work accident rates, but elsewhere what has been done generally falls well short of what is wanted and needed. The TUTB picks out eight specific areas where health at work strategies need beefing up. "